Morphology, Topography and Thickness of Copper Oxide Thin Films Deposited using Magnetron Sputtering Technique - Jia, Wei Low; Nafarizal, Nayan; Mohd Zainizan, Sahdan; Mohd Khairul, Ahmad; Ali Yeon, Md Shakaff; Ammar, Zakaria; Ahmad Faizal, Mohd Zain (2013)
Cupric Oxide (CuO) is one of the p-type metal oxide semiconductors that are suitable for use in gas sensing device. The copper oxide thin film was prepared on silicon wafer by sputtering of pure copper target at difference deposition time of 5 min, 10 min and 15 min using RF magnetron sputtering technique. Argon flow rate, oxygen flow rate, RF power and working pressure were fixed at 50 sccm, 8 sccm, 400 W and 22.5 mTorr, respectively. The influence of the deposition time towards the surface morphology, topography and thickness has been investigated. SEM and AFM analysis showed that the grain size of the films increases with the increase of deposition time. However, the surface structure of the films remains the same. In addition, it is noticed that when the deposition time increased, the surface of the films becomes rougher. The deposition rate was approximately 29 nm/min, and it was evaluated from the film thickness deposited at several times.